PEMBERDAYAAN ANAK PUTUS SEKOLAH DALAM PEMANFAATAN LIMBAH KULIT KOPI SEBAGAI PAKAN RUMINANSIA - Monika Linda; Muhammad Rifaldy; Rachmad Rachmad; Amira Mustarin (Jurnal Pendidikan Teknologi Pertanian, 2018)
Lembang Mesakada village is the most potential village in the plantation sector, especially coffee cultivation. Every year, the coffee farming community in Lembang Mesakada village is able to produce hundreds of tons of coffee beans. The high coffee harvest is what affects the amount of waste of coffee peel produced in coffee processing. The village of Lembang Mesakada itself has a total population of about 4,523. In this village the unemployment rate of out-of-school children is still very high due to uneven economic factors as well as the lack of motivation factors, as well as the lack of employment in the village that can change their lifestyle. The purpose of this activity is to provide employment to drop out children by utilizing waste from coffee skin so as to reduce environmental pollution and processed products can improve the welfare of the community, especially breeders, especially for ruminant livestock. The method used is the initial stage of preparation of tools and materials, Implementation Phase includes the stage of giving the material, the stage of making local microorganism (MOL), the mixing stage of the material, the fermentation stage, the feed drying stage, the feeding stage for livestock and the final stage of monitoring and evaluation. The result of the impact of activities for drop out children to ruminants produced is calculated based on responses in the form of questionnaires distributed with the number of respondents 20 people showed 68% are in very high category, 32% are in high category, and 0% are categorized as moderate and category low and very low 0%.